Role of anions for the reduction behavior of silver ions in polymer/silver salt complex membranes - Kim, JH; Kim, CK; Won, J; Kang, YS (ELSEVIER SCIENCE BV, 2005)
The reduction of silver ions to silver nanoparticles is an essential issue in polymer/silver salt complex membranes for facilitated olefin transport, because it has a critical influence on the long-term stability of membrane performance. In this study, the role of anions for the formation of silver nanoparticles in polymer/silver salt complexes was investigated. This role was assessed for the complexes of poly(N-vinyl pyrrolidone) (PVP) with three silver salts including AgBF4, AgCF3SO3, and AgNO3. Especially, UV irradiation to the membranes was used to clearly investigate the reduction behavior of silver ions. Separation performance test, UV-vis spectroscopy and transmission electron microscopy (TEM) clearly show that the reduction rate of silver ions strongly depends on the counteranions of salt, and has the following order: AgBF4 > AgCF3SO3 > AgNO3. This behavior of the formation of silver nanoparticles in polymer/silver salt complex membranes is explained in terms of the interaction strength of silver ions with the carbonyl oxygens of polymer, and that of silver ions with counteranions. It is concluded that when the former interaction is strong and the latter one is weak, the reduction rate of silver ions to silver nanoparticles is fast, and vice versa. These interactions were characterized using FT-IR, FT-Raman spectroscopy, and theoretical ab initio calculation. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: FACILITATED OLEFIN TRANSPORT; POLY(ETHYLENE OXIDE); PROPYLENE; NANOPARTICLES; EXCHANGE; ELECTROLYTES; PERMEATION; SEPARATION; MECHANISM; DENSITY